PENGELOLAAN JARINGAN DISTRIBUSI AIR BERSIH PERKOTAAN DI KABUPATEN GRESIK - Azhar Adi Darmawan; Ahmad Zamroni Ghozali; Chairil Saleh; Lourina Evanale Orfa; Dandy Achmad Yani; Wahyu Sejati (Universitas Trisakti, 2022)
Clean water is a need that has no limits and will continue to be sustainable for the community, so there is a need to concentrate on fulfilling it, especially in urban areas where clean water sources are usually difficult to obtain. In meeting the need for clean water, it is necessary to evaluate and plan for the development of the community's clean water needs so that they can be fulfilled optimally. The purpose of this study is to determine the need for clean water in urban areas where the study location is the management of the clean water distribution network system whose source of clean water comes from the Legundi IPA, Gresik Regency. The application used to support the analysis of clean water distribution network is EPANET software. Utilization of the program serves to analyze the flow of distributed water and can determine the pressure that occurs in each pipe and node. The evaluation results show an increase in clean water services for the Surabaya River Water Resources service area, Gresik Regency, from 39.78% in 2021 to 50.88% in 2031. Using the Least Square method, the projected population of the Legundi IPA Water Resources service area in 2031 numbered 131,555 people, with a division of nodes of 1278 nodes in 2020 to 1352 nodes in 2031 with pipe diameters of 2 inches to 24 inches. Meanwhile, the average need for clean water is 186.51 liters/second in 2020 to 285.04 liters/second in 2031.